Peningkatan Efektivitas Produksi UMKM Desa Jatisari melalui Edukasi Tata Kelola Persediaan dan Pelaporan Keuangan - Fitri Purnamasari (Universitas Muhammadiyah Malang, 2026)
Purpose – This community service activity was carried out with the aim of increasing the effectiveness of production and professionalism of Micro, Small and Medium Enterprises (MSMEs) in Jatisari Village, Tajinan District, Malang Regency. Design/methodology/approach – The program is implemented through educational and mentoring activities covering three main aspects: inventory management and strategies for determining the right target market. The community service team conducts a needs analysis through interviews with village officials and MSMEs, then provides education, learning modules, and entrepreneurial tips to improve production effectiveness and competitiveness. Findings – The results of the activity showed an increase in participants' understanding of the importance of inventory recording systems and production planning, although there are still challenges in implementing digital technology. Originality/value – This program is a concrete step in supporting village economic independence by increasing the capacity of local business actors, especially in Malang Regency.